Community Empowerment Through Digital Branding: Enhancing Pulau Ketam's Seafood and Herbal Product Marketing - Dian Septiana Sari; Annisa Ilmi Faried; Tuan Zamilah Binti Tuan Husain; Widia Br. Ginting (Proceeding of The International Conference on Business and Economics, 2025)
Pulau Ketam, a small fishing village in Selangor, Malaysia, faces persistent economic challenges despite its abundance of marine resources and longstanding tradition of herbal knowledge. Limited access to modern markets, dependence on middlemen, and a lack of digital literacy have restricted the community’s ability to fully benefit from its local assets. This study aims to explore the implementation of digital branding strategies as a means of empowering local communities and strengthening the marketing of seafood and herbal products. Employing a community-based participatory approach, the research integrates digital marketing training, brand development workshops, and the establishment of an e-commerce platform tailored to local needs. Data collection was carried out through surveys of 150 local entrepreneurs, focus group discussions with community leaders, and performance metrics analysis over a six-month period. The intervention generated a 65% increase in online sales, a 40% improvement in product visibility, and notable progress in community digital literacy. Findings reveal that structured digital branding programs not only enhance entrepreneurial capacity and market competitiveness but also support the preservation of cultural identity and traditional knowledge systems. This study contributes to the growing body of literature on rural digital transformation by providing empirical evidence that community empowerment through technology adoption can lead to sustainable economic development. The results suggest that similar models can be replicated in other marginalized communities to bridge digital gaps, strengthen local economies, and promote inclusive growth.